The association between airborne pollen monitoring and sensitization in the hot desert climate - Maryam A. Al-Nesf; Dorra Gharbi; Hassan M. Mobayed; Blessing Reena Dason; Ramzy Mohammed Ali; Salma Taha; Amjad Tuffaha; Mehdi Adeli; Hisham A. Sattar; Maria del Mar Trigo (Clinical and Translational Allergy, 2020)
Abstract Background Pollen is a major cause of allergic respiratory diseases. In Qatar, data on the presence and prevalence of allergenic airborne types of pollen is quite limited. Methods The study aimed to determine and correlate the most frequently implicated airborne pollen detected by aerobiological monitoring samplers in respiratory allergy symptoms. An aerobiological survey was started on May 8, 2017. Airborne pollen was collected using two Hirst type seven-day recorder volumetric traps. Skin prick test in patients attending allergy clinics in Doha using commercial extracts was conducted. Results Twenty-five pollen types representing the native, as well as the introduced plants, with a relatively low daily mean concentration were observed from May 2017 to May 2019. The highest pollen concentrations were reached by Amaranthaceae (58.9%), followed by Poaceae (21.7%). SPT revealed a comparatively higher degree of sensitization to pollen. Among 940 patients, 204 were sensitized to pollen (54% female) with 135 (66.2%) and 114 (55.8%) to Amaranthaceae and Poaceae, respectively. Some patients had polysensitization. There was a statistically significant association between Amaranthaceae, and asthma (r = 0.169, P = 0.016) and allergic rhinitis (r = 0.177, P = 0.012). Conclusions This is the first study to monitor airborne pollen in the state of Qatar. The main pollen detected were Amaranthaceae and Poaceae. Pollen may represent a possible exacerbating factor in adult patients with allergic diseases such as asthma and allergic rhinitis.